2020
DOI: 10.3389/fchem.2020.589769
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Natural Products Targeting SARS-CoV-2–ACE2 Receptor Interface – A MixMD Based HTVS Pipeline

Abstract: The COVID-19 pandemic, caused by novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a severe global health crisis now. SARS-CoV-2 utilizes its Spike protein receptor-binding domain (S-protein) to invade human cell through binding to Angiotensin-Converting Enzyme 2 receptor (ACE2). S-protein is the key target for many therapeutics and vaccines. Potential S-protein-ACE2 fusion inhibitor is expected to block the virus entry into the host cell. In many countries, traditional practices, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…It is a cosolvent simulation technique for identification of binding hots pots such as orthosteric, allosteric and cofactor binding sites as well as PPI sites [ 74 ]. Gopinath [ 75 ] used MixMD to detect potential inhibitor binding sites on S protein-ACE2 PPI interface. Drug-like organic probe molecules were added to the solvent to observe their localization in the simulation process, so as to detect the possible small molecule binding sites on the surface of S protein-ACE2 interface.…”
Section: Screening Methods For S Protein-ace2 Blockersmentioning
confidence: 99%
“…It is a cosolvent simulation technique for identification of binding hots pots such as orthosteric, allosteric and cofactor binding sites as well as PPI sites [ 74 ]. Gopinath [ 75 ] used MixMD to detect potential inhibitor binding sites on S protein-ACE2 PPI interface. Drug-like organic probe molecules were added to the solvent to observe their localization in the simulation process, so as to detect the possible small molecule binding sites on the surface of S protein-ACE2 interface.…”
Section: Screening Methods For S Protein-ace2 Blockersmentioning
confidence: 99%
“…Application of natural compounds with their wide pleiotropic effects provides an opportunity of controlling several mechanisms associated with SARS-CoV-2 infection with a high margin of safety. Since the emergence of COVID-19, several studies have shown the efficacy of such compounds as inhibitors [14][15][16][17]. Our earlier studies also identified the efficacy of plant-derived compounds on several cellular mechanisms of SARS-CoV-2 infectivity [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Most docking studies screening natural compounds against the spike protein have screened only a small number of ligands (≤200) and focus on the computational aspect alone [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] . Even larger-scale studies do not include experimental validation [41] , [42] , [43] . To address these limitations, we performed a structure-based docking study targeted at the regions of the spike receptor binding domain (RBD) involved in stabilisation of the Lys31 and Lys353 hotspots.…”
Section: Introductionmentioning
confidence: 99%